Pengaruh Harga, Kualitas, dan Citra Merek Terhadap Keputusan Pembelian Jasa Servis AC di Bengkel Tunas Toyota Latumenten - Sihombing, Aryon Douglas; Sirait, Tongam (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of price, service quality, and brand image on the purchasing decisions of AC service at Tunas Toyota Latumenten Workshop. Using a quantitative approach with multiple linear regression analysis on 200 respondents, the results reveal that all three variables significantly influence purchasing decisions simultaneously, with brand image exerting the strongest impact, followed by service quality and price. Service quality is a key factor in building customer loyalty through SERVQUAL dimensions such as reliability, responsiveness, and empathy. Toyota's strong brand image provides a competitive advantage by fostering trust and reputation among consumers. Meanwhile, price has the smallest impact, although perceived price fairness remains essential for customer satisfaction. The findings suggest managerial implications in the form of an integrative strategy involving brand reinforcement, service quality enhancement, and the application of value-based pricing. Further research is recommended using longitudinal approaches, mediating variables, and mixed-methods to deepen the analysis of consumer behavior in the automotive industry.